Study of the physical-chemical characteristics of non-food solid waste combustion; Journal of Physics: Conference Series; Vol. 1359 : Thermophysics and Physical Hydrodynamics - Larionov K. B. Kirill Borisovich; Tsibulskii (Tsibulskiy) S. A. Svyatoslav Anatolievich; Slusarskiy (Slyusarsky) K. V. Konstantin Vitalievich; Tolokolnikov A. A. Anton Andreevich; Gubin V. E. Vladimir Evgenievich (2019, 2019)
Title screen